Hubungan Pemberian Inisiasi Menyusu Dini dan Asi dengan Daya Tahan Tubuh Bayi di Puskesmas Tolo Kabupaten Jeneponto - Kasmawati Kasmawati; Asmaul Husnah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Colostrum, which is part of breast milk, contains immunoglobin M. Colostrum is breast milk that comes out a few days after giving birth and is clear or yellowish white. Objective: to determine the relationship between providing early initiation of breastfeeding and breast milk with the immune system of babies at the Tolo Health Center, Jeneponto Regency in 2020. The type of research used was a cross sectional study. The sample was 60 mothers who had babies aged 1-6 months who were in the working area of the Tolo Community Health Center, Jeneponto Regency. The results of the research show a relationship between giving early initiation of breastfeeding and the baby's immune system at the Tolo Community Health Center, Jeneponto Regency in 2020 with a p value = 0.024 < α 0.05. = 0.021 < α 0.05. Conclusion: there is a relationship between providing early initiation of breastfeeding and breast milk with the baby's immune system at the Tolo health center, Jeneponto Regency 2020. Suggestions: To increase knowledge and information for mothers about the importance of carrying out IMD immediately after the baby is born so that it can prevent antenatal deaths.